2012
DOI: 10.1016/j.foodchem.2011.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Some natural flavonoids are competitive inhibitors of caspase-1, -3, and -7 despite their cellular toxicity

Abstract: A common feature of both apoptosis and inflammation is the activation of caspases. Caspases are aspartate-directed cysteine proteases that have numerous cellular targets. It has been discovered that several flavonoids are inhibitors of caspases. Flavonoids are members of a family of polyphenolic compounds from plants that have many biological properties, one of which is the ability to induce cell death. Some flavonoids are selective inhibitors of particular caspases. Since some of the inhibitory flavonoids are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…Some authors suggest that apoptosis, induced in tumor cells by flavonoids, is not realized by caspase [26]. However, most authors think that flavonoids activate caspase 3 [4,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest that apoptosis, induced in tumor cells by flavonoids, is not realized by caspase [26]. However, most authors think that flavonoids activate caspase 3 [4,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Caspase activation appears to be involved in the progressive demise of the dopaminergic neurons resulting in PD pathogenesis. Previous studies have shown that flavonoids can function as specific activators or inhibitors of caspases 44,45 . Inhibitors against different caspases have been shown to rescue neuronal deaths in several experimental PD models 41,73 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, caspase inhibition has been shown to alleviate dopaminergic neuronal death in mammalian PD models. Flavonoids are known to regulate apoptotic pathways in both in vitro and in vivo disease models, including NDs 44,45 . Therefore, we aimed to determine the effects of GA and GB on the activation of caspase-3 responsible for inducing apoptotic cell death.…”
Section: Differential Regulation Of Caspase-dependent Cellular Death mentioning
confidence: 99%
“…Flavonoids have been demonstrated to exhibit anti-inflammatory, -allergic, -oxidative, -damage and -tumour effects (17,18). In recent years, studies on flavonoids have entered a new phase with these compounds revealed to inhibit proliferation of cancer cells, including breast, colon, lung, cervical and liver cancers and lymphoma cells (19)(20)(21)(22)(23). In addition, alpinetin has also been identified to inhibit proliferation of leukemic cells (24).…”
Section: Discussionmentioning
confidence: 99%